A Case of Growth Hormone Use in Dyggve–Melchior–Clausen Syndrome - Ravi Upadhyay; Claire Ruane; Rachel Umans; Beth A. Pletcher; Aditi Khokhar; Kristin Wong (Case Reports in Endocrinology)
Short stature has many causes including genetic disease, skeletal dysplasias, endocrinopathies, familial short stature, and nutritional deficiencies. Recombinant growth hormone (rGH) therapy may be employed to improve stature based on the underlying etiology and growth velocity. Skeletal dysplasia in Dyggve–Melchior–Clausen (DMC) syndrome tends to be progressive, typically with hip involvement, and ultimately leads to bilateral dislocation of the hip joints. Here, we present a pediatric patient with short stature treated with rGH therapy, complicated by the development of debilitating, bilateral hip pain, and found to have DMC syndrome. Our patient had limited range of motion at several joints including the hips after receiving 6 months of rGH therapy. Given the timing of the patient’s rGH therapy and the progression of her disease, it is difficult to determine if there were any benefits and instead, is concerning for worsening of her skeletal dysplasia with rGH therapy use. Consequently, patients with severe short stature should have a thorough workup for genetic causes like DMC syndrome, before initiating rGH therapy to determine any potential benefits or harms of treatment.